Belowground Bud Bank Responses to Grazing Intensity in the Inner‐Mongolia Steppe, China. (16th August 2014) - Qian, Jianqiang; Wang, Zhengwen; Liu, Zhimin; Busso, Carlos A.
Abstract: Despite the predominant role of bud banks in population regeneration and community dynamics, they have received far less attention than deserved. In particular, it remains unexplored how bud bank size and composition respond to different grazing intensities in grasslands. We investigated the size and composition of bud banks under different grazing intensities and regimes on a typical steppe in Inner Mongolia, China. Our results showed that (i) the total bud density in the traditional grazing regime (grazing and haymaking within the same year in the same paddock; 2, 444 ± 141 buds m −2 ) was 30 ± 11% higher (mean ± standard error; p < 0·05) than that in the mixed grazing regime (grazing and haymaking alternate annually in the same paddock; 1, 872 ± 109 buds m −2 ), but they did not change with increasing grazing intensity, (ii) rhizome buds and bulb buds decreased sharply ( p < 0·05) because of grazing in the mixed grazing regime, (iii) bud banks of rhizomatous grasses showed species‐specific responses to the increasing grazing intensity: decreasing in Leymus chinensis (Trin.) Tzvel., increasing in Agropyron cristatum (L.) Gaertn. and unresponsive in Carex duriuscula C. A. Mey. Data indicated that (i) the studied grazing intensities had no significant effects on the total bud bank, suggesting that belowground bud bank seems to be tolerant of grazing and (ii) the responses of bud bank to grazing differed with the bud bank type and species, indicating that bud banks could be used for explaining and predicting the dynamics of a natural grassland plant community. Copyright © 2014 John Wiley & Sons, Ltd.